2018
DOI: 10.1038/s42003-018-0186-4
|View full text |Cite
|
Sign up to set email alerts
|

Substrate specificity of plant nitrilase complexes is affected by their helical twist

Abstract: Nitrilases are oligomeric, helix-forming enzymes from plants, fungi and bacteria that are involved in the metabolism of various natural and artificial nitriles. These biotechnologically important enzymes are often specific for certain substrates, but directed attempts at modifying their substrate specificities by exchanging binding pocket residues have been largely unsuccessful. Thus, the basis for their selectivity is still unknown. Here we show, based on work with two highly similar nitrilases from the plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(53 citation statements)
references
References 47 publications
(56 reference statements)
2
45
2
Order By: Relevance
“…Branch 1 nitrilases (EC 3.5.5.1) (NITs) are industrially important 1 oligomeric enzymes (forming left-handed twists, spirals, turns or helices) that share a common architecture 28 and catalyze the hydrolysis of nitriles to carboxylic acids and ammonia and/or amides 9 . In all plants, the nitrilase 4 (EC 4.2.1.65) (NIT4) group represents the ancestral form, which is highly specific for β-cyano- l -alanine 10 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Branch 1 nitrilases (EC 3.5.5.1) (NITs) are industrially important 1 oligomeric enzymes (forming left-handed twists, spirals, turns or helices) that share a common architecture 28 and catalyze the hydrolysis of nitriles to carboxylic acids and ammonia and/or amides 9 . In all plants, the nitrilase 4 (EC 4.2.1.65) (NIT4) group represents the ancestral form, which is highly specific for β-cyano- l -alanine 10 .…”
Section: Introductionmentioning
confidence: 99%
“…It is thought that the NIT1 group enzymes evolved to catabolise the diverse glucosinolate-derived nitriles found in the Brassicaceae 1113 . Interestingly, plant NITs with high specificity against a single substrate or narrow group of substrates have evolved from the ancestral generalist NIT1 group enzymes 8,13,14 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…C surface is asymmetric interaction between two dimers, which plays an essential role in the formation of the spiral quaternary structure of nitrilases. It was reported that substitution of residues in the A and C surface could greatly alter the substrate specificity, thermostability, and activity of nitrilase (Sewell et al, ; Woodward, Trompetter, Sewell, & Piotrowski, ; Xu et al, ). The catalytic triads of Aa NIT and Br NIT were located at positions 65 and 66 (Glu), 152 and 153 (Lys), and 186 and 187 (Cys), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The flexible loops on the C surface of the wild-type BrNIT were replaced by a helix (residues 242-256) of BaNIT (as illustrated in Figure 5c). As the A and C surface play critical roles in the formation of the spiral quaternary structure of nitrilases (Thuku, Brady, Benedik, & Sewell, 2009), these changes may affect the conformation of higher-order spiral structure. What is more, a helix (residues 188-191) located near the catalytic residue Cys187 of the wild-type BrNIT disappeared in the chimera BaNIT (Figure 5b).…”
Section: Mechanism Of Enhanced Enzyme Propertiesmentioning
confidence: 99%